Javanese Language Maintenance in Ahmad Tohari’s Bekisar Merah: A Sosiolinguistics Analysis - Ines Ika Saputri; Endang Nurhayati (Humaniora, 2019)
This study aims to determine the form of Javanese language maintenance and to describe the factors motivating the use of Javanese language in Ahmad Tohari’s Bekisar Merah. This study will also discuss strategies of language maintenance in literature. The research herein applies descriptive qualitative methods. The results of this study show that the maintenance of Javanese language in Ahmad Tohari’s Bekisar Merah occurs in word forms, suluk, and Javanese philosophy. The factors motivating the use of Javanese language as a form of language maintenance in the novel are (1) the background of the author, and (2) the eﬀort to uphold Javanese language. Furthermore, there are two general strategies of Javanese language maintenance, particularly in literature, i.e. (1) literature spreading, and (2) authors’ loyalty to local languages as the manifestation of language maintenance.